Association of alpha2a and beta2 adrenoceptor expression with clinical outcome in breast cancer. (July 2014) - Du, Yueyao; Zhou, Liheng; Wang, Yaohui; Yan, Tingting; Jiang, Yiwei; Shao, Zhiming; Yin, Wenjin; Lu, Jinsong
Abstract Background: Alpha2-adrenoceptor (α2 AR) antagonists inhibit the growth of breast cancer cells. The action of beta2-adrenoceptors (β2 AR) on cell proliferation is still controversial. In this study, we investigated the association of α2a and β2 AR expression with tumor-relevant biological markers and clinical outcome. Methods: The expression of α2a and β2 AR was examined in paraffin-embedded samples of 220 operable breast tumors by immunohistochemistry. Associations between AR expression and tumor-relevant biomarkers were evaluated using the chi-square or Fisher's exact tests. Univariate analysis was modeled using Kaplan–Meier plots and multivariate analysis was modeled using the Cox test and adjusted for age, tumor size, lymph node status, and ER, PR and Her-2 status. Results: The α2a AR expression was associated with Her-2 status (P = 0.048) and a marginal significance was observed between α2a AR expression and ER (P = 0.061). In hormone receptor positive breast cancer patients, strong β2 AR expression correlated with better disease free survival (DFS) than weak expression (P = 0.031) and β2 AR (HR = 0.31, P = 0.039) and lymph node status (HR = 2.85, P = 0.031) were independent predictors of DFS on multivariate analysis. Conclusion: In hormone receptor positive breast cancer patients, strong β2 AR expression is correlated with better DFS than weak β2 AR expression and an interaction may exist between β2 AR and hormone receptor pathways. Some limitations of this study were the relatively small sample size and the intrinsic nature of retrospective study per se. Findings of the study are for hypothesis only and need to be confirmed in large prospective studies.